Lean development and innovation : hitting the market with the right products at the right time - Attolico, Luciano (Routledge, 2019)
Using Toyota's principles for product and process development, this book focuses the implementation of the Lean system during the past 10 years in dozens of corporations across various industries. The book highlights all steps on the journey from common trouble area to remarkable results. As it is written by a manager for other managers, it contains real work discoveries and insights. The author provides case studies from many different fields of application. The reader gains insight on US and European companies that successfully streamlined their innovation and product-development processes. These companies have overcome difficult periods and major challenges thanks to the ability to innovate with new Lean methodologies and, above all, a new workplace culture and mindset. The goal of this book is to help managers successfully apply Lean principles in the innovation and development area of their company while benefitting from the author's lessons learned during his many years of capitalized experience. This book provides a comprehensive framework that supports, step-by-step, the successful application of Lean principles in the innovation and development areas of the company. Readers learn how to drastically reduce the time required to develop products and discover and eliminate hidden costs and critical waste while increasing value for customers.